Perspective: Advancing spectator behavior research in youth sports through a closer examination of racial differences - Reynolds, Jerry F.; Chaney, Cassandra D.; Huffman, Olivia (Frontiers in Sports and Active Living, 2022)
Inappropriate spectator behaviors are a recognized challenge within both amateur and youth sport settings. These behaviors occur during youth sports contests and involve several sources of interaction, and impact the experience of child athletes, coaches, parents, and referees Spectator misconduct reflects a failure to self-regulate amidst disagreement with the coaching practices, officials, and poor performance from children. Despite widespread recognition of spectator misconduct and an emphasis by the United States Department of Health and Human Services (DHHS) to improve parent behavior, limited empirical research is available to promote understanding of both contributors to these actions, more specifically, what parents are observing from others and the frequency of such behaviors. A path to enhance research in this area is a closer examination of intersectionality, especially race and its influence upon parent observations and their personal behaviors as youth sport spectators. Based on research conducted in Louisiana, this perspective piece reflects on a study that found race as a contributing factor to differences in spectating behaviors of parents. The authors unpack the nuances of these findings through a lens of both Critical Race Theory (CRT) and implicit bias and provide a platform for future study, especially in states such as Louisiana where laws and the role of police have been advanced to mitigate spectator behaviors in youth sport settings.